2020
DOI: 10.5433/1679-0359.2020v41n3p865
|View full text |Cite
|
Sign up to set email alerts
|

Drying and storage of macaúba fruit: chemical and oxidative stability

Abstract: The objective of this study was to evaluate the chemical and oxidative stability of dried macaúba (Acrocomia totai) fruit in different air conditions and stored for up to 120 days. The macaúba fruits were collected, sanitized, dried at the temperatures of 40, 50, 60 and 70 °C and stored in raffia bags at room temperature. Drying at higher temperatures resulted in pulps with a darker and orangish color and pulp oil with lower titratable acidity contents and acidity indices. Throughout storage, there was an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
(13 reference statements)
1
6
1
Order By: Relevance
“…When positive, the values of a* and b* represent the red and yellow tones. Bocaiuva flour showed lower luminosity values than wheat flour and higher values of a* and b*, indicating yellowish color, possibly due to the presence of carotenoids, corroborating the results of Silva et al (2020).…”
Section: Pure Flours Of Wheat and Bocaiuvasupporting
confidence: 83%
See 2 more Smart Citations
“…When positive, the values of a* and b* represent the red and yellow tones. Bocaiuva flour showed lower luminosity values than wheat flour and higher values of a* and b*, indicating yellowish color, possibly due to the presence of carotenoids, corroborating the results of Silva et al (2020).…”
Section: Pure Flours Of Wheat and Bocaiuvasupporting
confidence: 83%
“…Bocaiuva flour also showed high moisture, carotenoid content and total phenols, compared with pure wheat flour (Table 1), and can be utilized to enrich wheat flour in the production of mixed flours. Silva et al (2020) also found high levels of carotenoids and antioxidant activity in bocaiuva flour.…”
Section: Pure Flours Of Wheat and Bocaiuvamentioning
confidence: 81%
See 1 more Smart Citation
“…A complementary study on the effects of storage period lengths on mesocarp quality parameters concludes that non-pre-treated, fully ripe fruits harvested directly from the bunch can be stored at room conditions for up to 20 days with oil quality remaining within desired limits (Tilahun et al 2019). With the aim of extending this period and avoiding deterioration of the mesocarp, a number of post-harvest methods were explored including the use of ozone gas on fresh fruits, irradiation, and air drying (da Silva et al 2020b;Silva et al 2019aSilva et al , 2019bTilahun et al 2020). Other studies investigated the applicability of new biocatalysts for hydrolyzing high-acid mesocarp oil (Rade et al 2020) and emerging oil extraction methods (da Rosa et al 2019b).…”
Section: A Short History Of Acrocomia Researchmentioning
confidence: 99%
“…It is worth noting that under good harvesting and storage practices, the acidification process of macauba pulp oil is slower than palm oil [55]. Other methods of treating the fruit immediately after harvest have been used to extend the shelf life of the fruit and the oil quality, including the use of ozone gas, irradiation, and different drying methods [53,57,58].…”
Section: From Macauba Fruit To Refined Oil: Modifications 31 Fruit Pr...mentioning
confidence: 99%